Intermediary liability and trade in follow-on innovation - Cuntz, Alexander; Sahli, Matthias (World Intellectual Property Organization, 2021)
Liability rules affect the incentives of intermediaries to disseminate and curate creative works, in particular when works build on the work of predecessors and they are potentially infringing copyright. In an application to the visual arts, we show that appropriation artists borrow images from different sources and incorporate them into new, derivative works of art. By doing so, they risk infringing copyright but also put commercial trade and availability of the work at litigation risk as liability can extend to intermediaries in markets (auction houses) or in public exhibitions (museums). Using a differences-in-differences model and unique data on the level of the individual art work, we empirically investigate the impact of the prominent 2013 Cariou v. Prince U.S. court decision on trade and availability in Appropriation Art.
"October 2021."
Keywords: Appropriation (Art); Copyright.